Mobile Pulmonary Rehabilitation: Feasibility of Delivery by a Mobile Phone-Based Program - Whittaker, Robyn; Dobson, Rosie; Candy, Sarah; Tane, Taria; Burrowes, Kelly; Reeve, Julie; Tawhai, Merryn; Taylor, Denise; Robertson, Trina; Garrett, Jeffrey; Humphrey, Gayl; Brott, Tamzin; et al. (Frontiers in Computer Science, 2021)
Background: Pulmonary rehabilitation (PR) has been proven effective but is not well accessed due to transport, time, cost, and physical limitations of patients. We have developed a mobile phone-based PR program (mPR) that could be offered as an alternative for those unable to attend in-person. This was developed following formative research with patients, their families and clinicians. mPR has a core text message program plus an app that includes an action plan, exercise videos, lung visualization, symptom score questionnaire and 1-min sit-to-stand test. Aims: To determine the feasibility of delivering pulmonary rehabilitation by mobile phone. Methods: A 9-week non-randomized (1-arm) pilot study was conducted. Participants were 26 adults with chronic obstructive pulmonary disease plus four family members, who were offered participation at first assessment or during group PR sessions. Outcomes included satisfaction, engagement with the program, and perceived impacts. Results: Eight people (31%) opted for text messages only, and 18 (69%) chose text messages plus the app. Three people stopped the program early, 20 said they would recommend it to others, 19 said it helped them to feel more supported, 17 said it helped them to change their behavior. Conclusion: It is feasible to deliver PR support via mobile phone, including exercise prescription and support. Our mPR program was appreciated by a small number of people with chronic respiratory disorders and family members. Suggestions for improvements are being used to inform the further development of the program, which will then be tested for effectiveness. Registered with the Australia New Zealand Clinical Trials Registry ACTRN12619000884101 (www.anzctr.org.au).